Doctor Who. The complete eleventh series [videorecording (Blu-Ray)] - Whittaker, Jodie, 1982-; Walsh, Bradley, 1960-; Cole, Tosin (Warner Bros. Home Entertainment : BBC, 2019)
The dazzling Thirteenth Doctor falls out of the sky just in time to thwart an alien huntsman who is stalking human prey. With little time to spare and the population of Sheffield (and Earth!) at risk, the Doctor recruits three new friends, gentle Ryan, no-nonsense Yasmin and Ryan₂s step-grandfather, Graham, who soon feel more like family than companions. Join the foursome in ten fresh and enormously thrilling rollercoaster adventures across time and the universe.